Lowered oxidative capacity in spinal muscular atrophy, Jokela type; comparison with mitochondrial muscle disease - Ratia, Nadja; Palu, Edouard; Lantto, Hanna; Ylikallio, Emil; Luukkonen, Ritva; Suomalainen, Anu; Auranen, Mari; Piirilä, Päivi (Frontiers in Neurology, 2023)
Introduction Spinal muscular atrophy, Jokela type (SMAJ) is a rare autosomal dominantly hereditary form of spinal muscular atrophy caused by a point mutation c.197G>T in CHCHD10. CHCHD10 is known to be involved in the regulation of mitochondrial function even though patients with SMAJ do not present with multiorgan symptoms of mitochondrial disease. We aimed to characterize the cardiopulmonary oxidative capacity of subjects with SMAJ compared to healthy controls and patients with mitochondrial myopathy. Methods Eleven patients with genetically verified SMAJ, 26 subjects with mitochondrial myopathy (MM), and 28 healthy volunteers underwent a cardiopulmonary exercise test with lactate and ammonia sampling. The effect of the diagnosis group on the test results was analysed using a linear model. Results Adjusted for sex, age, and BMI, the SMAJ group had lower power output (p < 0.001), maximal oxygen consumption (VO2 max) (p < 0.001), and mechanical efficiency (p < 0.001) compared to the healthy controls but like that in MM. In the SMAJ group and healthy controls, plasma lactate was lower than in MM measured at rest, light exercise, and 30 min after exercise (p ≤ 0.001–0.030) and otherwise lactate in SMAJ was lower than controls and MM, in longitudinal analysis p = 0.018. In MM, the ventilatory equivalent for oxygen was higher (p = 0.040), and the fraction of end-tidal CO2 lower in maximal exercise compared to healthy controls (p = 0.023) and subjects with SMAJ. Conclusion In cardiopulmonary exercise test, subjects with SMAJ showed a similar decrease in power output and oxidative capacity as subjects with mitochondrial myopathy but did not exhibit findings typical of mitochondrial disease.